Block transaction premia and partial private benefits: An empirical investigation - Giovanna Nicodano; Alessandro Sembenelli (Fondazione Eni Enrico Mattei (FEEM), 1997)
Following Zwiebel (1995) and Zingales (1995) the block premium is related to the share of total control rents which is being transferred through a block transaction relative to the share of control rents enjoyed by the market. The former share is measured by the difference in the seller's (the buyer's) power index before and after the transaction. Unobservable control rents are estimated by resorting to balance sheet figures which, according to the literature on corporate control, should be correlated with them. Estimates of such a pricing equation are based on a sample of block transactions of listed Italian companies. Implied control rents are also recovered.
Keywords: G32; G12; G34; 330; Shapley values; Control rents; Ownership structure